From Majelis Ta'lim to Character-Building Families: Religious Strengthening by BKMT Hamparan Rawang - Pefriadi, Pefriadi; Yusuf, Muhammad (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2023)
This study is based on the fact that moral decay in society seems to be an inevitable reality in this era of scientific and technological advancement, especially among families. Therefore, the role of BKMT is not only as a non-formal educational institution for acquiring knowledge, but it must also be able to provide learning that encourages the development of strong character. In an effort to internalize character education values, BKMT Hamparan Rawang Subdistrict presents various activities carried out during religious study sessions. This study aims to describe the strengthening of religious character in families through BKMT Hamparan Rawang Subdistrict. This study uses a qualitative approach with descriptive analysis methods. Data collection techniques include observation, interviews, and document analysis. The results of this study indicate that the strengthening of religious character in families through BKMT Hamparan Rawang District, through its work programs, includes: weekly, monthly, and annual religious study sessions, conducted consistently, using lecture and question-and-answer methods.